2010
DOI: 10.1007/s10640-010-9423-0
|View full text |Cite
|
Sign up to set email alerts
|

Interview Effects in an Environmental Valuation Telephone Survey

Abstract: Abstract.Because of the lack of markets for many environmental services, economists have turned to valuation surveys to estimate the value of these services. However, lack of market experience may cause respondents in valuation surveys to be more prone to interview effects than they would be with other opinion surveys. Without reference to market price or experience, respondents are less likely to have well-defined preferences, which may cause respondents to be more easily influenced by the interview process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…For example, while Lusk (2003) finds that cheap talk eliminated bias amongst ordinary consumers, there is no such evidence when considering the sample of knowledgeable consumers. Similar insights are reported in a number of other framed field experiments, see e.g., List (2001), Aadland andCaplan (2003, 2006), and Blumenschein et al (2008).…”
Section: Aligning Hypothetical and Real Statements Of Value: The Rolesupporting
confidence: 87%
See 1 more Smart Citation
“…For example, while Lusk (2003) finds that cheap talk eliminated bias amongst ordinary consumers, there is no such evidence when considering the sample of knowledgeable consumers. Similar insights are reported in a number of other framed field experiments, see e.g., List (2001), Aadland andCaplan (2003, 2006), and Blumenschein et al (2008).…”
Section: Aligning Hypothetical and Real Statements Of Value: The Rolesupporting
confidence: 87%
“…Loureiro and Lotade (2005) find that WTP for eco-labeled products are approximately 128.6 to 177.9 percent greater amongst subjects approached by an interviewer from a region that produces the products. Gong and Aadland (2009) find that monthly WTP for curbside recycling was approximately 7 -8% higher amongst respondents interviewed by a Caucasian or a woman.…”
Section: Aligning Statements Of Value: Social Isolation and Interviewmentioning
confidence: 80%
“…Among others, McKenzie (1977), Riphahn and Serfling (2005), and Gong and Aadland (2011) confirm the relevance of matched respondent-interviewer characteristics with respect to, e.g., gender, and race. Our evidence supports that matching the interview participants on migration background and education can yield a significantly lower propensity of welfare underreporting.…”
Section: Estimation Resultsmentioning
confidence: 66%
“…Based on our understanding of the communities from our previous surveys, our fieldworkers interviewed participants during the week and at weekends as potential participants were at work or school during the week. Some literature sources such as Gong and Aadland (2011) suggest that participants are more likely to participate in a survey if they are approached between 5 pm and 9 pm on weeknights and not over the weekend. While this may be true for some contexts, and not for others such as in the South Africa context, it may highlight the importance and need for a comprehensive formative phase, prior to implementation, to establish the most ideal times to conduct fieldwork.…”
Section: Limitationsmentioning
confidence: 99%
“…Blohm, Hox, and Koch (2006) found that fieldworkers who emphasise the importance of a survey are less successful in persuading potential respondents to participate in a survey than those who do not. According to the Social Attribution Model, respondents edit their responses to conform to what they perceive to be the interviewer's norms and expectations based purely on the interviewer's observable characteristics (Gong & Aadland, 2011).…”
Section: Introductionmentioning
confidence: 99%